Al-Nahda dan Munculnya Aliran-Aliran pada Sastra Arab Modern - Hasan, Insanul; Ferdinal, Ferdinal (English Study Program, Faculty of Humanities, Universitas Andalas, Padang, 2024)
This article aims to uncover the emergence of various streams of Arabic literature during the Al-Nahda period along with the phenomena that underlie it. This research is a literature review study that uses descriptive analysis methods. The results of this research indicate that the revival of Arabic literature from its decline marks the beginning of the modern period. The turning point occurred when Napoleon Bonaparte's expansion reached Egypt in 1798, providing Egypt with the opportunity to come into contact with Western culture. One of the impacts of this meeting is on the development of Arabic literature. The development of Arabic literature is inseparable from this phenomenon, certainly with characteristics and traits that distinguish it. Arabic literature underwent a transformation that distinguishes it from previous periods. In the Modern phase, various movements emerged in Arabic literature in succession. The emergence of this movement is due to criticisms of the literary models that came before it or to refine the movements that emerged in earlier times. This article will focus on three movements: Neo-Classical, Romanticism, and Realism.